Etika dan Tanggung Jawab Sosial dalam Investasi Saham Properti - Anggraini, R. A Sri Fadhilah; Sudarwan, Alwi; Siahaan, Peri Harianto; Wibowo, Prasetio; Siregar, Emiel Salim (Innovative: Journal Of Social Science Research, 2025)
The capital and investment needed for the development cannot be met only by the government and national private sector. Therefore, it is necessary to encourage maximum efforts to attract investment in Indonesia from abroad. In this case, the legal research conducted by the researcher is by using the normative type, where the problem approach is the case approach. Regarding the data sources obtained, where primary data comes from Laws and Decisions, secondary data comes from law books, tertiary data comes from KBBI. Legal regulations on investment through shares in the property business sector in Indonesia involve a number of regulations that regulate how property companies can receive investment from shareholders, both individuals and legal entities, both from within the country and abroad. Therefore, in general, legal regulations on investment through shares in the property business sector involve a combination of regulations regarding foreign investment, capital markets, taxes, building permits, and protection for investors. Every investor, both domestic and foreign, must comply with these provisions to carry out legitimate investments and in accordance with applicable laws in Indonesia. Legal protection for investment in the form of shares in the property business sector is very important to ensure legal certainty and security for investors. Overall, investment in shares in the property sector receives legal protection that includes aspects of shareholder rights, compliance with licensing regulations, and efforts to prevent practices that are detrimental to investors.